SISTEM PEMICU EXCELLENT KARYAWAN PADA KANTOR KEMENTRIAN HUKUM DAN HAM SUMATERA UTARA - Ahmad Zakir; Maulida Sri Putri; Yulia Agustina Dalimunnthe; Tantri Hidayanti Sinaga (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
In this system, the company is currently developing many ways by the company to do the assessment in a computerized way. companies are required to follow business competition so companies must develop human resources with their respective supervisors or directors. Trigger employee evaluation is one of the techniques that will be applied so as to provide information to superiors to reward the quality of human resources who have done a good job. This research will develop a superior company trigger system using Android-based media. The system implemented can be used by superiors to determine the best employees in accordance with the value of the work performed by each employee. The purpose of this research is to study and develop the system that is currently running in order to become even better at doing employees. The results of this study include android-based applications in conducting employee talks that can facilitate superiors.